A novel ionic liquid degumming process for Apocynum venetum. Issue 11 (1st November 2016) - Yang, Fengrui; Ma, Yingchong; Qian, Yongfang; Lv, Lihua; Zheng, Laijiu; Zhao, Yuping
Abstract : A novel degumming process for Apocynum venetum was presented using ionic liquid (IL)–water mixture in the paper. Optimum performance for the degumming of Apocynum venetum fiber was obtained in 80% (m/m) 1-butyl-3-methylimidazolium acetate ([BMIM][Ac]) at a temperature of 130 °C for 6 h, and the solution was maintained at the liquor ratio 1:20. The Apocynum venetum fibers before and after degumming were characterized by Scanning electron micrographs, Fourier transform infrared spectroscopy, and X-ray diffraction. The result showed that the Apocynum venetum fibers degummed with IL were longer than traditional chemical method, and the breaking strength of fiber with IL degumming process was significantly improved in comparison with traditional chemical method. Therefore, the IL–water degumming for Apocynum venetum fibers could dissolve the gum of fibers, and improve the spinnability of Apocynum venetum distinctly.